MEDICAL MANAGEMENT OF A CLOSED TYPE PYOMETRA USING MISOPROSTOL AND CLOPROSTENOL COMBINATION IN A PUG - PATI, R R; UMAMAGESWARI, J; SRIDEVI, P (The Indian Journal of Animal Reproduction, 2022)
A female pug had the history of dullness, depression, inappetance for one week and was crossed 20 day earlier in her first heat. The clinical examination revealed mild congested and dry vaginal mucus membrane without any vaginal discharge. Ultrasound examination revealed multiple anechoic sacculations. The case was diagnosed as closed cervix pyometra and was treated with Misoprostol and PGF2α combination. The female pug showed an uneventful recovery subsequent to treatment.